Efektivitas Teka-Teki Silang sebagai Media Pendidikan Kesehatan tentang Kesehatan Gigi dan Mulut pada Siswa Sekolah Dasar di Samarinda - Nino Adib Chifdillah; Adinda Gusti Nurhaliza; Yona Palin; Dini Indo Virawati (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Oral health is a global health issue among children. The study aimed to analyze the effect of health education using crossword puzzles on knowledge about oral health among students at SDN 006 Loa Janan Ilir. The study was a pre-experimental study using an one-group pretest-posttest design. The intervention involved health education using crossword puzzles as a medium. The sample consisted of 79 fifth-grade students selected through total sampling. Data were collected through questionnaires and analyzed statistically using the Wilcoxon test. The validity of the questionnaire was tested by comparing the calculated r-value with the table r-value. The questionnaire validity test used Cronbach's Alpha value. The research results showed that most respondents were 11 years old (63 students, 79.7%), female (45 students, 57%), had parents with a secondary education level (40 students, 50.6%), and had never received information about KGM (64 students, 81%). The number of students with good knowledge increased by 56 (80.9%). Meanwhile, the number of students with adequate knowledge decreased by 44, and the number of students with insufficient knowledge decreased by 12. Statistical analysis results indicated that there was an effect of the intervention on respondents' knowledge (ρ-value=0.000). Crossword puzzles was effective as a health education media about oral health for elementary school students.